Triple negative breast cancer: 5-year results of combined treatment - Ostapenko, Valerijus; Pipirienė Želvienė, Teresė; Smailytė, Giedrė; Ostapenko, Andrej; Meškauskas, Raimundas (Acta medica Lituanica, 2014)
Background. Breast cancer is the most common female cancer worldwide. It is a heterogeneous disease with regard to biological behaviour, responses to treatment and prognosis. The term “triple negative breast cancer” (TNBC), namely, refers to the immunohistochemical classification of breast tumours lacking ER, PgR, and HER2 protein expression. TNBC does not respond to endocrine therapy and chemotherapy remains the main systemic therapeutic option in the adjuvant and metastatic setting of TNBC. The aim of this study was a retrospective analysis of the results of combined treatment for TNBC. Patient and methods. In our retrospective analysis, we analized 431 patients with TNBC treated with combination therapy from March 2005 until December 2009 at the Institute of Oncology, Vilnius University. 52.20% of the whole group of patients were women older than 50 years. Stage I was diagnosed in 23.9%, stage II in 49.65%, stage III in 22.74%, stage IV in 3.71% of cases. According to pathological types of the tumour ductal invasive carcinoma was diagnosed in 376 patients (87.24%) and tumour grade G3 was determined in 330 patients (76.57%). All 431 patients underwent surgical treatment, 239 patients had chemotherapy (55.45%). The disease-free survival and overall survival were estimated by the Kaplan-Meier method. The Log-rank test was used for survival comparison between the groups. P